The politics of Islamophobia : race, power and fantasy - Tyrer, David (London : Pluto Press, 2013)
"Despite its emblematic place within contemporary racism and its increasingly important position in defining relations between states and ethnicised minorities, Islamophobia remains a contested, frequently unrecognised and largely under-theorised form of racism. The Politics of Islamophobia provides a definitive contribution to these debates, offering a theoretically sophisticated account which draws upon a series of substantive case studies to position Islamophobia as an expression of racialised governmentality"--Provided by publisher.
Framing Islamophobia -- Now you see me : fantasy and misrecognition -- Once more, with feeling : Islamophobia and racial politics -- Post-politics and Islamophobia -- Democrat, moderate, other -- Islamophobia beyond the war on terror -- Questions, questions, questions : reframing Islamophobia.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 650
Keywords: Islam and politics; Islam -- Public opinion; Islamophobia; SOCIAL SCIENCE -- Discrimination & Race Relations; SOCIAL SCIENCE -- Minority Studies; POLITICAL SCIENCE / History & Theory; Electronic books